EKSPLORASI STRUKTUR BERBAHAN DASAR CORRUGATED PAPER UNTUK KEMASAN TELUR AYAM - Fatmanto, Gricelda Khalilah; Maharani, Vania Isabella; Putri, Sheila Andita (SENADA (Seminar Nasional Manajemen, Desain dan Aplikasi Bisnis Teknologi), 2024)
Packaging is a container used to increase the function and value of a product; apart from that, product packaging design is the main reason for buyers to buy a product. Packaging design is an important element in showing a product's image, one of which is egg packaging, which requires packaging design to protect and present the image of the egg product itself. This research was carried out using a qualitative method by dropping egg packaging that had been made from a height of 1.5 meters, and it had to be ensured that the eggs in the packaging did not break from the egg packaging that had been made using corrugated paper. The aim of designing packaging designs for eggs is to develop new variations of packaging designs, especially in terms of structures that can protect egg packaging products, in order to attract consumer interest and make it easier for consumers to consume them.